PERAN SISTEMATIKA MIKROBIA DALAM MENGUNGKAP KEANEKARAGAMAN MIKROORGANISME - Idramsa, Idramsa (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACTDiversity of bacteria and archaea  can not be learned completely   yet not identified perfectly. This is due to the abundant amount of diversity of microorganisms. The existence of molecular technologies allow to identify quickly and accurately the organism. Classification approach is based on the value of character and phylogenetic fenetik make a meaningful classification of microorganisms. Microbes such as bacteria systematic approach should be based on systematic polyfasik. Kata Kunci : Klasifikasi, fenetik, filogenetik, sistematika mikrobia